SUSTAINABLE MSMEs PERFORMANCE: OVERVIEW OF HUMAN RESOURCES, INFORMATION TECHNOLOGY, AND MANAGEMENT ACCOUNTING INFORMATION - Willy Nurhayadi; Mega Arum (International Journal of Economy, Education and Entrepreneurship, 2023)
With the assistance of the Internet of Things (IoT), Micro, Small, and Medium Enterprises (MSMEs) will have an easier time marketing their goods and services in the era 4.0 of the industrial revolution. Therefore, MSMEs must prepare the quality of their human resources, technology, and systems to improve their business performance and compete in the current digitalization era. This study aims to measure the extent to which the quality of human resources owned by SMEs, as well as the technology and systems they have, with the system here being management accounting information to understand the significance of recording and bookkeeping, as well as providing more comprehensive and structured information regarding a company's operations and its financial position